Image personification in children`s music in the context of compositions by S. Prokofiev, P. Plakidis and J. Karlsons - Vecumnieks, Andris (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Article aims to explore the issues of image personification and show its practical implementation possibilities in music practice. The purpose of the article – to assess compositions of S. Prokofiev, P. Plakidis and J. Karlsons. Using analytical and comparative research methods, I will try to show the differences in personification in S. Prokofiev's symphonic story “Peter and the Wolf”, P. Plakidis` symhonic fairy tale “The Steadfast Tin Soldier” un J. Karlsons` “Rural Suite” for symhonic orchestra.